NATURAL GAS: A LONG BRIDGE TO A PROMISING DESTINATION (Utah Environmental Law Review; Vol 32 No 2 (2012), 2012)
Supporters of efforts to replace hydrocarbons with carbon-free renewable resources as our primary source of electricity often refer to natural gas as a “bridge fuel.”   That reference reflects a reluctant recognition that renewable resources cannot replace hydrocarbons as our primary generating fuel in the near term. It also reflects recognition that, while natural gas is a hydrocarbon, it is less damaging to the environment than other fossil fuels. In particular, displacement of coal with natural gas as a generating fuel reduces emissions of greenhouse gases, such as carbon dioxide, by about 50%. Thus, the “bridge fuel” metaphor refers to the expectation of many policy makers that we can move in the direction needed to mitigate climate change in the near term by displacing coal with natural gas, but that we will replace all hydrocarbons with carbon-free renewable resources in the long term. My goal is to explore and to critique the assumptions that underlie the bridge fuel metaphor. I begin by focusing on the length of the bridge that natural gas is likely to provide. I conclude the natural gas bridge to carbon-free fuels is likely to be extremely long, at least decades and probably a century. I then explore the question of what we are likely to find at the end of that bridge. Is it metaphorically like the “bridge to nowhere” the senator from Alaska famously (or infamously) inserted as an earmark in an appropriations Bill? I conclude that, while the “bridge” will not take the U.S. everywhere we would like to go, it is likely to take the U.S. to a destination that is a major improvement over the status quo, measured with reference to any plausible set of national or international goals.